1994
DOI: 10.1080/00207149408409347
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Changes During Hypnosis: A Heart Rate Variability Power Spectrum Analysis as a Marker of Sympatho-Vagal Balance

Abstract: Spectral analysis of beat-to-beat variability in electrocardiography is a simple, noninvasive method to analyze sympatho-vagal interaction. The electrocardiogram is analyzed by means of an automatic, autoregressive modeling algorithm that provides a quantitative estimate of R-R interval variability by the computation of power spectral density. Two major peaks are recognizable in this specter: a low-frequency peak (LF, -0.1 Hz), related to the overall autonomic activity (ortho+parasympathetic) and a high-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 17 publications
5
53
3
2
Order By: Relevance
“…In their study, Aubert et al [18] found that in healthy individuals LF levels were decreased in the hypnosis group while HF was increased and LF/HF rate was decreased. DeBenedittis et al [19] found similar results in healthy individuals undergoing hypnosis. Yuksel et al [20] demonstrated that in women HRV decreased during hypnosis.…”
Section: Discussionsupporting
confidence: 71%
“…In their study, Aubert et al [18] found that in healthy individuals LF levels were decreased in the hypnosis group while HF was increased and LF/HF rate was decreased. DeBenedittis et al [19] found similar results in healthy individuals undergoing hypnosis. Yuksel et al [20] demonstrated that in women HRV decreased during hypnosis.…”
Section: Discussionsupporting
confidence: 71%
“…It has for instance been suggested, that hypnosis reduces the clinical signs of inflammation after tuberculin injection [31], presumably due to increased parasympathetic activity after hypnosis [32,33]. Furthermore, there are several case reports of hemiplegic patients that do not develop arthritis or lose arthritis activity on the affected side [34,35].…”
Section: Rheumatoid Arthritis: Pathogenesis Disease Characteristics mentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation of the PFC, based on the central role of the mPFC in cognitive theory of mind, can cause changes in acute pain perception and has been used in a model of central sensitization syndrome such as fibromyalgia (Mhalla, et al 2011;Short, et al 2011) but no data have been currently published in IBS patients. Modulation of the ANS by restoring the sympatho-vagal balance (DeBenedittis, et al 1994;Nishith, et al 2003;Gemignani, et al 2006) as well as modifying coping strategies vigilance state and globally the restoration of a functional brain-gut axis, are at the origin of the efficacy of these treatments. Brain imaging techniques have shown modulation of brain activation, as for example in the amygdala, by such treatments (Goldin and Gross 2010;Lawrence, et al 2011).…”
Section: Therapeutic Implications-treatment Targeting Amygdala Activimentioning
confidence: 99%